Marriage and Employment Participation with Wage Bargaining in Search Equilibrium - Roberto Bonilla; Alberto Trejos (Center for Economic Studies and ifo Institute (CESifo), 2017)
The empirical literature addressing links between the labor and the marriage markets is numerous and varied. Despite this, the theoretical (equilibrium) literature that explicitly links the two markets is less developed, particularly so with frictional markets. We build an equilibrium search model where married couples make joint decisions on home production and labor market participation. We then analyze the implications of our results for a frictional marriage market allowing us to consider the interaction between both markets. A workers bargaining position reflects their own productivity, and also the employment status and conditions of their spouse. We find that couples with very different productivities have different strategies regarding labor market participation. In symmetric couples, the partners behave symmetrically. Workers get better job offers when their spouses are employed, and in some equilibria a person may search for transitory jobs with the sole purpose of raising the long-term wages of their spouse. In some cases, firms unilaterally increase a worker's wage in order to reduce turnover, by ensuring that the spouse stays at home. Whether firms follow that strategy or not may be a matter of multiple equilibria, depending on parameter values. All this provides an additional explanation for wage and search behavior heterogeneity of similar workers and/or couples.
Keywords: D13; J12; J22; J31; 330; labour market participation; wage formation; marriage market; linked frictional markets